2013
DOI: 10.1159/000348399
|View full text |Cite
|
Sign up to set email alerts
|

Altered Fractional Anisotropy in Early Huntington's Disease

Abstract: Huntington's disease (HD) is a dominantly inherited neurodegenerative disease best known for chorea. The disorder includes numerous other clinical features including mood disorder, eye movement abnormalities, cognitive disturbance, pendular knee reflexes, motor impersistence, and postural instability. We describe a mild case of HD early in the disease course with depression and subtle neurological manifestations. In addition, we review MRI and diffusion tensor imaging features in this patient. The bicaudate ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Changes in white matter detected through imaging are one of the first signs of disease in people with HD (PwHD) (Rosas et al, 2006;Paulsen et al, 2008;Paulsen, 2009;Hobbs et al, 2010;Di Paola et al, 2012;Phillips et al, 2013;Singh et al, 2013;Matsui et al, 2015;Odish et al, 2015;Poudel et al, 2015;Faria et al, 2016;Bourbon-Teles et al, 2019;Tereshchenko et al, 2019;Sweidan et al, 2020;Oh et al, 2021). Morphometric studies of postmortem HD brain showed reduced cross-sectional area of white matter in addition to gray matter atrophy (de la Monte et al, 1988;Vonsattel and DiFiglia, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in white matter detected through imaging are one of the first signs of disease in people with HD (PwHD) (Rosas et al, 2006;Paulsen et al, 2008;Paulsen, 2009;Hobbs et al, 2010;Di Paola et al, 2012;Phillips et al, 2013;Singh et al, 2013;Matsui et al, 2015;Odish et al, 2015;Poudel et al, 2015;Faria et al, 2016;Bourbon-Teles et al, 2019;Tereshchenko et al, 2019;Sweidan et al, 2020;Oh et al, 2021). Morphometric studies of postmortem HD brain showed reduced cross-sectional area of white matter in addition to gray matter atrophy (de la Monte et al, 1988;Vonsattel and DiFiglia, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in white matter detected through imaging are one of the first signs of disease in people with HD (PwHD) ( Bourbon-Teles et al, 2019 ; Di Paola et al, 2012 ; Faria et al, 2016 ; Hobbs et al, 2010 ; Matsui et al, 2015 ; Odish OF et al, 2015 ; Oh et al, 2021 ; Paulsen, 2009 ; Paulsen et al, 2008 ; Phillips et al, 2013 ; Poudel et al, 2015 ; Rosas et al, 2006 ; Singh et al, 2013 ; Sweidan et al, 2020 ; Tereshchenko et al, 2019 ). Morphometric studies of postmortem HD brains showed reduced cross-sectional area of white matter as well as gray matter atrophy ( de la Monte et al, 1988 ; Vonsattel and DiFiglia, 1998 ).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in tensor-derived indices located in the right caudate nucleus in our study was in line with the reverse changes as reported by Gatto and Weissmann (2019) . This might be potentially attributed to the surrounding white matter loss which caused the appearance of comparatively more organized striatal gray matter ( Douaud et al, 2009 ; Singh et al, 2013 ). Studies on preclinical mouse models have indicated that cortical neuronal death is not proportionally accompanied by white matter tract degeneration ( Rattray et al, 2013 ), and early white matter changes are a main feature of neuronal and axonal connectivity impairment in fluorescent-tagged animals ( Gatto et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%